Potential utilization of hazardous mining wastes in the production of lightweight aggregates. Issue 1 (2nd January 2018) - Park, Hyunsik; Ha, Minchul; Shin, Doyun; Kim, Minseok; Sohn, Il
ABSTRACT: Lightweight aggregates from mixtures of gold tailing, red mud and waste limestone were produced using a high-temperature sintering process. Raw materials were quantitatively analyzed, and hazardous materials were identified by chemical analysis. An oxide system corresponding to the major components of the mining waste was carefully designed based on the CaO–FeO x –Al2 O3 –SiO2 quaternary system similar to lightweight aggregates. Sintering, softening and melting behaviour of the sample was investigated to optimize the sintering conditions. After heating, specimens were analyzed to clarify its sintering mechanism. Phase change during sintering was observed by X-ray diffraction, and the effect of temperature on the structural unit changes of the specimen was confirmed by Fourier transform-infrared spectroscopy. Microscopic analysis by scanning electron microscope-energy dispersive X-ray analysis was carried out to identify the morphological changes of the sample. Physical properties of the specimen were measured, and the compressive strength was improved with less water absorption.